Fulfillment Facility Cost Ferry Port Side Of Mainland District Ketapang Banyuwangi East Java Based Communications Km Number 52 Of 2004 - Bambang Setiawan; Purboyo Purboyo; Ady Yanto Saputro (IWJ : Inland Waterways Journal, 2022)
Ketapang Port is managed by PT. ASDP Indonesia Ferry (Persero) Ketapang branch which serves 2 routes with different tollgates. Ketapang Port is a connecting route between Banyuwangi Regency, East Java Province with Jembrana Regency, Bali Province and Banyuwangi Regency, East Java Province with West Lombok Regency, West Nusa Tenggara Province. at the port is still not complete. This can disrupt the smooth operation of the port. Based on the results of the analysis, there are several problems with the main facilities on the mainland side of the Ketapang Port of Ketapang – Lembar such as the Pernumpang terminal not yet available, weighbridge is not available, there is no separation of passenger and vehicle entry access. When passengers go to/from the ship (gangway), there is no field. delivery/pickup parking and not yet optimal parking lot ready to load Lintas Ketapang – Lembar. In order for services at the Ketapang Crossing Port to run smoothly, which is supported by maximum land-side basic facilities, efforts can be made, namely procurement of passenger terminals so that port operational activities are more optimal, Procurement of weighbridge facilities so that vehicle tonnage can be limited according to the maximum limit. wharf, provision of gangway facilities so that passengers have their own lane so as to improve passenger safety when from/to the ship. provision of delivery/pick-up parking facilities so that delivery/pick-up vehicles can be accommodated, and provision of vehicle class separators in the ready-to-load parking lot Ketapang – Lembar.